Nitrogen topdressing timing modifies the gluten quality and grain hardness related protein levels as revealed by iTRAQ. (30th March 2019) - Zhong, Yingxin; Wang, Weiling; Huang, Xin; Liu, Mingming; Hebelstrup, Kim Henrik; Yang, Donglei; Cai, Jian; Wang, Xiao; Zhou, Qin; Cao, Weixing; Dai, Tingbo; Jiang, Dong
Highlights: The iTRAQ identified 591 proteins into 17 categories in mature grain flour. N topdressing timing regulated expressions of 97 proteins in 11 biological processes. Gliadins and HMW-GS were more sensitive to N topdressed timing than LMW-GS. Delaying topdressed N altered grain hardness and flour allergic protein content. Change of N topdressing timing from jointing stage caused grain yield loss. Abstract: Nitrogen fertilization regimes significantly affect both grain quality and yield. Wheat plants were subjected to different application timing of topdressed nitrogen at the emergence of the top fifth (TL5), top third (TL3) and top first leaf (TL1), respectively. The iTRAQ (isobaric tag for relative and absolute quantitation) technology was adopted to obtain the complete proteome of wheat flour and to identify the differentially expressed proteins (DEPs) as regulated by nitrogen topdressing timing. Collectively, 591 proteins into 17 functional categories in flour of mature grains were identified. In comparison to TL3, 50 and 63 DEPs were identified in TL5 and TL1, respectively. Nine of the DEPs commonly dependent on nitrogen topdressing timing are the γ-gliadins or high-molecular-weight glutenin subunits. Additionally, delaying nitrogen topdressing modified the grain hardness and allergic protein content. The results suggested that altering nitrogen topdressing timing is a potential strategy for pursuing targeted processing quality of wheat flour.